Distribusi Pembelajaran melalui Lagu pada Buku Tematik Kelas Rendah Sekolah - Irma Inesia Sri Utami; Iyon Muhdiyati (Program Studi Pendidikan Guru Sekolah Dasar, Universitas Muhammadiyah Sukabumi, 2020)
A joyful on the learning process makes the achievement of learning objectives easy to be achieved. Sometimes learning is placed as a game for low grade students, especially singing. Singing activities are popular for lower class students before entering the primary school. This study aims to determine the frequency of the songs contained in the integrated thematic book of the 2013 revision curriculum. This research was conducted using the quantitative content analysis method on 24 thematic books published by the Ministry of Education and Culture in 2017. The research data were analyzed by grouping the songs being taught. The research findings were validated in two ways, namely internal and external. Internal validation was done by triangulating data sources. External validation is done by using all members of the population as a sample. The results of the study revealed that learning through songs in low grades gradually decreased in quantity. Further research is suggested to determine the extent to which songs can provide learning content from a syntactic, semantic, pragmatic and / or hermeneutic point of view.